Efficacy of specific antivenom and fresh frozen plasma in reversing Daboia palaestinae venom‐induced hemostatic derangement. Issue 4 (26th June 2020) - Nivy, Ran; Aroch, Itamar; Bruchim, Yaron
Abstract: Objectives: To evaluate the in vitro efficacy of specific Daboia (Vipera) palaestinae ( Dp ) antivenom or fresh frozen plasma (FFP) against Dp venom‐induced hemostatic changes Design: In vitro study. Setting: Laboratory of a university referral hospital. Animals: Five healthy dogs. Interventions: Rotational thromboelastometry (including recombinant tissue factor or kaolin activators [EXTEM and INTEM, respectively]) and conventional hemostatic tests were evaluated in citrated whole blood samples that underwent 4 treatments: (1) no additives (control); (2) 15 μg of Dp venom; (3) 15 μg of Dp venom and 10 μL of specific Dp antivenom; (4) 15 μg of Dp venom and 0.3 mL of FFP. A linear mixed‐effects regression model was used to compare results between each treatment and the control. Measurements and main results: Dp ‐venom engendered statistically significant ( P  < 0.05) EXTEM changes in 8/17 variables, all indicative of hypercoagulability, which were negated by antivenom but not with FFP. Similarly, Dp ‐venom induced hypercoagulable, hyperfibrinolytic changes in 12 of 17 INTEM variables, of which only 5 of 12 were negated by antivenom but not with FFP. Fibrinogen concentration was decreased, and the activated partial thromboplastin time (aPTT) was shortened ( P < 0 .05 for both) in all treatments compared to the control. Conclusions: This study demonstrated the ephemeral procoagulant phase of Dp envenomation for the first time. Many venom‐induced thromboelastometric changes were reversed by specific antivenom but not with FFP. Prospective clinical studies are warranted to investigate whether the present findings translate to clinical efficacy.